Community, network or both? Towards a holistic approach to studying online social structures - Yanchenko, Kostiantyn (Communication & Language at Work, 2019)
This paper overviews scientific narratives surrounding communities and networks both off- and online and criticizes the dichotomous approach to the topic, according to which each social structure can be classified as either a community or a network. It is argued that such a division does not facilitate comprehension of the contemporary online social structures with their complexity and dynamism. The study provides an alternative view on the issue assuming that community and network are not mutually exclusive concepts and can be studied holistically. The proposed theoretical statement is operationalized and piloted on the example of ‘Aarhus Internationals’ Facebook group – an online venue for international expats in Denmark. A content analysis of the group`s posts showed how exactly community and network aspects of social structures may coexist and interact online.